Change of algal organic matter under different dissolved oxygen and pressure conditions and its related disinfection by-products formation potential in metalimnetic oxygen minimum. (1st November 2022) - Han, Jingru; Cao, Ruihua; Li, Kai; Wang, Shuo; Ji, Gang; Xu, Huining; Wang, Jingyi; Huang, Tinglin; Wen, Gang
Highlights: The changes of M. aeruginosa IOM and its DBPFPs under MOM were investigated. The decrease of IOM and DBPFPs was faster under aerobic condition. Protein- and humic-like fluorescence could be used as DBPFPs alternative index. The activity and diversity of microorganisms were lower under anoxic condition. The lower dissolved oxygen in MOM was not conducive to the decomposition of IOM. Abstract: Most of the reservoirs or lakes will form a metalimnetic oxygen minimum (MOM) with the characterization of a substantial fraction of dissolved oxygen (DO) depleted below the epilimnion. The effect of intracellular organic matter (IOM) of algal cells transformed under MOM conditions is completely different from that of the original IOM on water quality. In this study, the IOM changes of Microcystic aeruginosa under different MOM conditions and its related disinfection by-products formation potentials (DBPFPs) were investigated by changing the pressure and DO concentration of MOM. Total Fmax increased slightly and then decreased under different pressure conditions, finally decreasing by no more than 22.0%. Under aerobic condition, dissolved organic carbon (DOC) and total Fmax decreased significantly, and decreased by 60.4% and 38.8% within the first 2 days. The results of specific UV absorbance (SUVA) and UV250 /UV365 indicated that aromatic compounds and average molecular weight of IOM were gradually increased under different MOM conditions. The total DBPFPs increased firstly and then decreased under different pressure conditions, and finally decreased by 26.2%-33.1%. The decrease of total DBPFPs was significantly higher under aerobic condition than that under anoxic condition, which finally decreased by 64.5%. Redundancy analysis showed that the fluorescence parameter (protein-like and humic-like fluorescence) could be expected as an index to predict the DBPFPs. Moreover, the results revealed that with the decrease of DO, the activity and diversity of natural microbial consortium decreased, which prevented the further degradation and utilization of organic matter by natural microbial consortium. Therefore, lower DO was a key player for the deterioration of water quality under MOM conditions. Graphical abstract: Image, graphical abstract